Milrinone in heart failure. Effects on exercise haemodynamics during short term treatment. - Timmis, A D (1985)
The effects of milrinone, a new bipyridine inotropic agent, on the haemodynamic responses to treadmill exercise were studied in 12 patients with congestive heart failure. Four weeks' treatment with milrinone 20 mg daily produced an improvement in left ventricular function during exercise as reflected by significant increments in cardiac index and stroke volume index without change in pulmonary capillary wedge pressure. Systemic oxygen consumption, measured at submaximal exercise, also increased suggesting that the drug induced rise in stroke output was associated with improved skeletal muscle perfusion. Maximum exercise capacity increased. Importantly, the beneficial effects of milrinone on exercise haemodynamics and exercise tolerance were sustained throughout the four week treatment period. No drug related side effects occurred. After treatment with milrinone was stopped left ventricular function deteriorated to a level slightly, but significantly, worse than that before treatment. These observations indicate a potentially useful role for milrinone in treating heart failure.